2018
DOI: 10.1007/s10506-018-9236-y
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised and supervised text similarity systems for automated identification of national implementing measures of European directives

Abstract: The automated identification of national implementations (NIMs) of European directives by text similarity techniques has shown promising preliminary results. Previous works have proposed and utilized unsupervised lexical and semantic similarity techniques based on vector space models, latent semantic analysis and topic models. However, these techniques were evaluated on a small multilingual corpus of directives and NIMs. In this paper, we utilize word and paragraph embedding models learned by shallow neural ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 24 publications
2
13
0
2
Order By: Relevance
“…Figure 3 presents the macro-average precision, recall and F-Score for the mappings between directive (sub-)articles and NIM provisions.These results indicate that the Luxembourg directive mappings consistently achieved a higher recall, precision and F-Score than Italian and English ones for all the similarity measures. This is consistent with the research presented in [12]. The best overall macro-average F-Score values are 0.8243, 0.7276 and 0.6712 for mappings between directive (sub-)articles and the NIM provisions of Luxembourg, Italy and Ireland respectively.…”
Section: Mappings Between Directive (Sub-)articles and Nim Provisionssupporting
confidence: 90%
See 2 more Smart Citations
“…Figure 3 presents the macro-average precision, recall and F-Score for the mappings between directive (sub-)articles and NIM provisions.These results indicate that the Luxembourg directive mappings consistently achieved a higher recall, precision and F-Score than Italian and English ones for all the similarity measures. This is consistent with the research presented in [12]. The best overall macro-average F-Score values are 0.8243, 0.7276 and 0.6712 for mappings between directive (sub-)articles and the NIM provisions of Luxembourg, Italy and Ireland respectively.…”
Section: Mappings Between Directive (Sub-)articles and Nim Provisionssupporting
confidence: 90%
“…A multilingual parallel corpus of 43 directives and their corresponding NIMs from Luxembourg, Ireland and Italy (15,400 norms) was presented in [12]. This corpus only contains mappings between directive (sub-)articles and NIM provisions.…”
Section: Corpus Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Such national implementation of international law is particularly common in Europe where directives of the supranational European Union (EU) are being implemented through national measures within the organization's member states. While the EU currently tasks specialized consulting companies to manually monitor the faithful implementation of such directives, researchers have shown that text-based similarity measures can identify national implementing statutes with reasonable accuracy across different EU member states (Nanda et al, 2018).…”
Section: ) Legislative Draftingmentioning
confidence: 99%
“…Так, в 2007 г. в качестве онтолингвистического ресурса была обоснована характеристика знаний DALOS и система организации знаний (KOS) для обеспечения контроля и поддержки законодательного процесса в многоязычной среде европейских стран, обязанных имплементировать евродирективы в национальное право [1]. В 2019 г. были представлены результаты разработки и апробации моделей на данных, обеспечивающих контроль над имплементацией европейского права в национальные правовые системы; эти модели были реализованы с использованием неконтролируемых методов лексического и семантического сходства, основанных на моделях векторного пространства, скрытом семантическом анализе и тематических моделях [88].…”
Section: правовые информационные системы контрольного назначенияunclassified